La obra de Carlo Ginzburg y su significado dentro de los estudios históricos contemporáneos - Aguirre Rojas, Carlos Antonio (Revista Inclusiones, 2022)
Nowadays the work of Carlo Ginzburg can be considered, as a classic of the universal historiography. None of his books, articles and lectures can be avoided for the apprentice who learn about history and for the Clío’s muse lover, who is consecrated. The Microhistory-in spite of Ginzburg hardly mentions it in his writing- He speaks from the botton of the human being. Without it we can’t understand the Macrohistory and without this understanding, the evolution of the human being: the History